Effect of Chain Length on Swelling Transitions of Brodie Graphite Oxide in Liquid 1‐Alcohols - Artem Iakunkov; Andreas Nordenström; Nicolas Boulanger; Gui Li; Christoph Hennig; Mads Ry Vogel Jørgensen; Innokenty Kantor; Alexander V. Talyzin (Advanced Materials Interfaces, 2024)
Abstract Swelling is the most fundamental property of graphite oxides (GO). Here, a structural study of Brodie graphite oxide (BGO) swelling in a set of long chain 1‐alcohols (named C11 to C22 according to the number of carbons) performed using synchrotron radiation X‐ray diffraction at elevated temperatures is reported. Even the longest of tested alcohols (C22) is found to intercalate BGO with enormous expansion of the interlayer distance from ≈6Å up to ≈63Å, the highest expansion of GO lattice ever reported. Swelling transitions from low temperature α‐phase to high temperature β‐phase are found for BGO in all alcohols in the C11–C22 set. The transitions correspond to decrease of inter‐layer distance correlating with the length of alcohol molecules, and change in their orientation from perpendicular to GO planes to layered parallel to GO (Type II transitions). These transitions are very different compared to BGO swelling transitions (Type I) found in smaller alcohols and related to insertion/de‐insertion of additional layer of alcohol parallel to GO. Analysis of general trends in the whole set of 1‐alcohols (C1 to C22) shows that the 1‐alcohol chain length defines the type of swelling transition with Type I found for alcohols with C<10 and Type II for C>10.